2019
DOI: 10.5530/ijcep.2019.6.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heart Rate Variability in Early Post-menopausal Women

Abstract: Background and Aim: Menopause marks to a point in time that follows after the permanent stoppage of menstruation. Menopausal transition includes various autonomic dysfunctions. Age is known to affect autonomic function. Therefore, in the present study the effect of menopause on autonomic function has been assessed by comparing the heart rate variability parameters between early postmenopausal and late premenopausal women. Methods: Premenopausal and postmenopausal women of age group between 40-55 years were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[20] HRV was also found to be altered in early postmenopausal women with increased Low frequency, decreased high frequency component and decreased LF/HF ratio. [9] Cardiac Autonomic Function Test (CAFT)…”
Section: Sympathovagal Imbalancementioning
confidence: 99%
See 1 more Smart Citation
“…[20] HRV was also found to be altered in early postmenopausal women with increased Low frequency, decreased high frequency component and decreased LF/HF ratio. [9] Cardiac Autonomic Function Test (CAFT)…”
Section: Sympathovagal Imbalancementioning
confidence: 99%
“…[1] SVI is observed in postmenopausal women. [9] Large RCTs in older women showed decrease in cognitive function. [4] Thus, SVI and decline in cognitive function are present in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Also, sympathovagal imbalance is observed in post-menopausal women with increased sympathetic activity and reduced parasympathetic activity which adds to the cardiovascular risk. [4] Heart rate variability is a sensitive measure of sympathovagal imbalance. [4] It is found that there is a decline in heart rate variability in post-menopausal women.…”
mentioning
confidence: 99%
“…[4] Heart rate variability is a sensitive measure of sympathovagal imbalance. [4] It is found that there is a decline in heart rate variability in post-menopausal women. [5] Recent study shows that post-menopausal state also offers higher risk of developing metabolic syndrome with an increased level of insulin resistance.…”
mentioning
confidence: 99%